High image quality watermarking model by using genetic algorithm - Mohammed, Ghassan N.; Yasin, Azman; Zeki, Akram M. (2012)
Imperceptibility or quality for digital image watermarking represents one of the most important requirements for any digital watermarking system. Many studies try to enhance the quality by using different techniques and methods. In this study, Genetic Algorithm (GA) method is used to embed two bits of watermarking data within every pixel of original image and to find the optimal value based on the existing Dual Intermediate Significant Bit (DISB). However, if the two embedded bits is equal to the original bits then this means the watermarked image is still the same as the original one without any changing, while in the other case GA is used getting the minimum fitness value in which the fitness is the absolute value between the pixel and chromosome and the value of chromosome between 0-255. The results show that the new method improves the image quality and get the optimal value for the two embedded bits.